(untitled) (Historia, 2021)
As a library consultant and bibliographer, this reviewer was commissioned in 2012 by the Nelson Mandela Foundation to create an inventory of the images and video recordings featuring Nelson Mandela, many of which were taken or recorded worldwide. The collection includes framed photographs of Mandela with Bill Clinton; some with other dignitaries; several of Mandela’s wife, Winnie, and many others. During my Financial Times of London newspaper days, I attended a conference at the Nelson Mandela Foundation. As Mr Mandela neared the exit door, he called out to me, saying: “Are you not coming to greet me?” The “shy me” went up to greet him, as he is my elder (p iii).